Anomalus dan Brand Aura Karakter Superhero Pada Film Gundala: Analisis Struktur Naratif - Joko Utomo Hadibroto (CoverAge: Journal of Strategic Communication, 2019)
This research or analysis uses Vladimir Propp's narrative structure analysis of the genre of superhero film titled Gundala, which is based on Indonesian comics. Gundala is a superhero character or hero who has supernatural powers that come from the energy of lightning. Through the power of his lightning energy, Gundala as a hero is able to defeat villain as a criminal. This is the narration presented from the film Gundala. Thus, the use of the concept of narrative structure aims to reveal the role and position of each character in the frame of binary opposition. Next, an understanding of his supernatural powers was analyzed using the concept of anomalous categories from Claude Levi-Strauss. Furthermore, the film Gundala has its appeal in presenting the narratives of the characters. Both superhero and villain characters. Related to that, the use of the concept of brand aura aims to find an element of attraction for the characters of the shop for the cinema audience.